Investigation of SOST gene polymorphisms in postmenopausal Turkish women: a preliminary study - Ozkan, Zehra Sema; Deveci, Derya; Yuce, Huseyin (Elsevier Sci Ltd, 2011)
[Abstract Not Available]
European Biotechnology Congress -- SEP 28-OCT 01, 2011 -- Istanbul, TURKEY